High-contrast grating reflectors for 980 nm vertical-cavity surface-emitting lasers - Gebski, M. (2018)
This paper presents results of computer simulation of 1D monolithic high refractive index contrast grating (MHCG) reflector also called surface grating reflector (SGR). We analyzed optical properties of the GaAs reflector designed for 980 nm wavelength with respect to the grating parameters variation. We also determined the electric field patterns after reflection from the structure in several cases of parameters variation. We show that thanks to the scalability and design simplicity, proposed design is a promising candidate for simple, next generation vertical cavity surface emitting lasers emitting from ultra-violet to infrared.